Multi-input Multi-output Fuzzy Logic Controller for Complex System: Application on Two-links Manipulator. (2015) - Baghli, Fatima Zahra; bakkali, Larbi El; Lakhal, Yassine
Abstract: The robot manipulator is a mechanical system multi-articulated, in which each articulation is driven individually by an electric actuator, it is the most robot used in industry, this system need an efficient control strategy, such as Fuzzy Logic law control, by means each articulation is controlled independently, this kind of control present a lot of inconvenient, such as error of each articulation, isn't taken account into others. In this present work, we present a Multi-Input Multi-Output Fuzzy controller (MIMO) to ensure the articulation robot control strategy, the results obtained present satisfactory and shows clearly the efficiency of the present Fuzzy-MIMO controller.